In Vitro Effect of Porphyromonas gingivalis Methionine Gamma Lyase on Biofilm Composition and Oral Inflammatory Response - Stephen, Abish S.; Millhouse, Emma; Sherry, Leighann; Aduse-Opoku, Joseph; Culshaw, Shauna; Ramage, Gordon; Bradshaw, David J.; Burnett, Gary R.; Allaker, Robert P. (PLOS ONE, 2016)
Methanethiol (methyl mercaptan) is an important contributor to oral malodour and periodontal tissue destruction. Porphyromonas gingivalis, Prevotella intermedia and Fusobacterium nucleatum are key oral microbial species that produce methanethiol via methionine gamma lyase (mgl) activity. The aim of this study was to compare an mgl knockout strain of P. gingivalis with its wild type using a 10-species biofilm co-culture model with oral keratinocytes and its effect on biofilm composition and inflammatory cytokine production. A P. gingivalis mgl knockout strain was constructed using insertion mutagenesis from wild type W50 with gas chromatographic head space analysis confirming lack of methanethiol production. 10-species biofilms consisting of Streptococcus mitis, Streptococcus oralis, Streptococcus intermedius, Fusobacterium nucleatum ssp polymorphum, Fusobacterium nucleatum ssp vincentii, Veillonella dispar, Actinomyces naeslundii, Prevotella intermedia and Aggregatibacter actinomycetemcomitans with either the wild type or mutant P. gingivalis were grown on Thermanox cover slips and used to stimulate oral keratinocytes (OKF6-TERT2), under anaerobic conditions for 4 and 24 hours. Biofilms were analysed by quantitative PCR with SYBR Green for changes in microbial ecology. Keratinocyte culture supernatants were analysed using a multiplex bead immunoassay for cytokines. Significant population differences were observed between mutant and wild type biofilms; V. dispar proportions increased (p<0.001), whilst A. naeslundii (p<0.01) and Streptococcus spp. (p<0.05) decreased in mutant biofilms. Keratinocytes produced less IL-8, IL-6 and IL-1α when stimulated with the mutant biofilms compared to wild type. Lack of mgl in P. gingivalis has been shown to affect microbial ecology in vitro, giving rise to a markedly different biofilm composition, with a more pro-inflammatory cytokine response from the keratinocytes observed. A possible role for methanethiol in biofilm formation and cytokine response with subsequent effects on oral malodor and periodontitis is suggested.